Perceived difficulty in the theory of planned bahavior percieved behavioral control or affected attitude? - Kraft, Pal; Rise, Jostein; Sutton, Stephen; Roysamb, Espen (2005)
A Study was conducted to explore (a) the dimensional structure of perceived behavioral control (PBC),(b) the conceptual basis of perceived difficulty items, and (c) how PBC components and instrumental and effective attitudes, respectively, relate to intention and behavior. The material stemmed from a two-wave study of Norwegian graduate students (N=227 for the prediction of intention and N=110 for the prediction of behavior). Data were analysed using confirmatory factor analysis (CFA) and multiple regression by the application of structural equaling modelling (SEM). CFA suggested that PBC could be conceived of as consisting of three separates but interrelated factors (perceived control, perceived confidence and perceived difficulty), or as two separate but interrelated factors representing self-efficacy (measured by perceived difficulty and perceived confidence or by just perceived confidence) and perceived control. However, the perceived difficulty items also overlapped substantially with affective attitude. Perceived confidence was a strong predictor of exercise intention but not of recycling intention. perceived control, however, was a strong predictor of recycling intention but not exercise intention. Affective attitudes but not instrumental attitudes were identified as substantial predictors of intentions. the findings suggest that at least under some circumstance it may be in adequate to measure PBC by means of perceived difficulty. One possible consequence may be that the role of PBC as a predictor of intention is somewhat overestimated, whereas the role (affective) attitude may be similarly underestimated.